2012
DOI: 10.1590/s0100-29452012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Phyllochron estimation in intercropped strawberry and monocrop systems in a protected environment

Abstract: RESUMO -O filocrono é definido como o tempo necessário para o aparecimento de folhas sucessivas em uma planta, caracterizando o crescimento e o desenvolvimento vegetal e, com isso, a adaptação da planta ao ambiente. Para verificar o desenvolvimento e a adaptação de cultivares de morangueiro consorciadas com a figueira, foi estimado o filocrono nesse sistema e no cultivo solteiro. O trabalho foi realizado em duas estufas agrícolas, na Universidade de Passo Fundo (28º15'41'' S, 52º24'45'' W e 709 m), no período … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
0
18
0
3
Order By: Relevance
“…Tazzo et al, (2015) found phyllochron values of 135.61° C day leaf -1 for the Albion cultivar, which is higher than what was seen for Camarosa. For the Albion cultivar, Costa et al, (2012) observed differences in phyllochron of vernalized and non-vernalized seedlings and the appearance of leaves on vernalized seedlings was 93.30° C day leaf -1 , while for nonvernalized seedlings, the phyllochron was 117.80° C day leaf -1 . The lower leaf emission rate in a plant resulted in higher phyllochron which means that plants likely needs a greater thermal sum for leaf emission (Rose et al, 2013).…”
Section: Variable Phyllochronmentioning
confidence: 81%
“…Tazzo et al, (2015) found phyllochron values of 135.61° C day leaf -1 for the Albion cultivar, which is higher than what was seen for Camarosa. For the Albion cultivar, Costa et al, (2012) observed differences in phyllochron of vernalized and non-vernalized seedlings and the appearance of leaves on vernalized seedlings was 93.30° C day leaf -1 , while for nonvernalized seedlings, the phyllochron was 117.80° C day leaf -1 . The lower leaf emission rate in a plant resulted in higher phyllochron which means that plants likely needs a greater thermal sum for leaf emission (Rose et al, 2013).…”
Section: Variable Phyllochronmentioning
confidence: 81%
“…Phyllochron variability among cultivars was also verified by Clerget et al (2008) and Rosa et al (2009) in wheat and by Pržulj and Momčilović (2013) in barley. Furthermore, in assessing the phyllochron in strawberry, Rosa et al (2011) andMendonça et al (2012) observed differences among cultivars. According to these authors, different results among cultivars are due to genetic differences.…”
Section: Resultsmentioning
confidence: 99%
“…Studies to determine the phyllochron were performed for crops, such as sorghum (Clerget et al 2008), brachiaria (Santos et al 2009), maize Martins et al 2012), wheat (Rosa et al 2009;Mohamed et al 2013;Pržulj and Momčilović 2013), and strawberry (Rosa et al 2011;Mendonça et al 2012). Researches for determination of leaf appearance rate were carried out for the crops brachiaria (Santos et al 2009;Paciullo et al 2008), maize (Streck et al 2010), and wheat (Mohamed et al 2013).…”
Section: Gg Chaves Et Al Introductionmentioning
confidence: 99%
“…The base temperature (Tb) is defined as the daily thermal time units above a lower base temperature, below which the plant does not grow or its development is so slow that it can be ignored (Rosa et al, 2011), for the strawberry evaluation a 7 °C as a base temperature (Mendonça et al, 2012).…”
Section: Methodsmentioning
confidence: 99%